The income of the Swedish baby boomers - Lennart Flood; N. Anders Klevmarken; Andreea Mitrut (Institute for the Study of Labor (IZA), 2006)
This paper studies the income of Swedish households belonging to the baby boom generation, i.e. those born in the 1940-50. An international comparison as well as an historical presentation of income patterns is given. However, the main purpose is to generate the future income of the baby boom generation as they get older. A major result is that the income standard of the young-old will become much higher than that of the very old. If our simulations bear the stamp of realism, they suggest that we will see new and large poverty in Sweden among the very old in the future. The pension system contributes to this result. The front loaded design gives with its reduced wage indexation a higher income immediately after retirement but a much lower income at older age. From this perspective it is unfortunate that so much attention is given to the discussion of replacement rates. The replacement rate, although interesting in itself, completely misses the long run effect and just provides a comparison of incomes shortly after with incomes before retirement. If we instead focus on the relative income of older pensioners, the results become quite different. Our results challenge the conception of a sustainable pension system. If the relative income of older pensioner's drops and at the same time expenditures for health and care increase, one might wonder how the old in our society will make both ends meet. If pensions become too small to meet minimum standards, the requirement of financial sustainability of the pension system results in an increasing financial burden on other parts of the general social protection system.
urn:nbn:de:101:1-20090622358
Keywords: 330; Bevölkerungsentwicklung; Intergenerative Belastungsrechnung; Alterssicherung; Lebensstandard; Schweden